2015
DOI: 10.1038/srep15727
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fluxes at the root-soil interface show a mismatch of nitrogen fertilizer supply and sugarcane root uptake capacity

Abstract: Globally only ≈50% of applied nitrogen (N) fertilizer is captured by crops, and the remainder can cause pollution via runoff and gaseous emissions. Synchronizing soil N supply and crop demand will address this problem, however current soil analysis methods provide little insight into delivery and acquisition of N forms by roots. We used microdialysis, a novel technique for in situ quantification of soil nutrient fluxes, to measure N fluxes in sugarcane cropping soils receiving different fertilizer regimes, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 56 publications
2
76
0
1
Order By: Relevance
“…Akumulasi hara tersebut termineralisasi bertahap dan digunakan oleh tanaman padi secara berturut-turut. Secara umum aplikasi pupuk N hanya sekitar 50 % yang dapat ditangkap oleh tanaman, sisanya menjadi polusi melalui run off, leaching dan emisi gas nitrogen (Brackin et al, 2015). Tabel Hasil penelitian Sun et al (2015) menunjukkan bahwa kombinasi aplikasi pupuk NPK dengan pupuk organik secara signifikan meningkatkan kelimpahan komunitas mikrobia yang terlibat dalam siklus nitrogen yaitu bakteri nifH, archaeal dan bacterial amoA, nirS, nirK dan nosZ.…”
Section: Kadar Unsur Hara Tanahunclassified
“…Akumulasi hara tersebut termineralisasi bertahap dan digunakan oleh tanaman padi secara berturut-turut. Secara umum aplikasi pupuk N hanya sekitar 50 % yang dapat ditangkap oleh tanaman, sisanya menjadi polusi melalui run off, leaching dan emisi gas nitrogen (Brackin et al, 2015). Tabel Hasil penelitian Sun et al (2015) menunjukkan bahwa kombinasi aplikasi pupuk NPK dengan pupuk organik secara signifikan meningkatkan kelimpahan komunitas mikrobia yang terlibat dalam siklus nitrogen yaitu bakteri nifH, archaeal dan bacterial amoA, nirS, nirK dan nosZ.…”
Section: Kadar Unsur Hara Tanahunclassified
“…The present study's soil has a low CEC, thus the relatively higher NUE reported would be mainly associated to the retention of fertilizer N by soil microbial biomass, which was favoured by the high C:N ratio of soil organic matter. The slower N turnover through microbial and organic pools would be more closely matching root N uptake (Brackin et al 2015), increasing fertilizer N recuperation by the plant.…”
Section: Nitrogen Use Efficiencymentioning
confidence: 99%
“…According to Brackin et al (2015), the increase in mineral N availability after fertilization exceed in several orders of magnitude (200 to 3,000%) the N uptake by sugarcane roots. The N in excess is retained by charged soil particles, lost from the system or immobilized by soil microorganisms.…”
Section: Nitrogen Use Efficiencymentioning
confidence: 99%
“…Moreover, an arrested development of roots had substantial effects on the nutrient uptake and organic composition of crops20212223. Except for root disruption, other underground parts were directly inhibited by soil compaction for underground crops2425.…”
mentioning
confidence: 99%